Influence of lunar semidiurnal tides on groundwater dynamics in estuarine aquifers - Zhang, Xiaoying; Dong, Fan; Dai, Heng; Hu, Bill X.; Qin, Guangxiong; Li, Dan; Lu, Xiaoshu; Dai, Zhenxue; Soltanian, Mohamad Reza (Springer, 2020)
The influence of lunar semidiurnal tides on coastal groundwater aquifers has been conceptualized for decades. However, a thorough understanding of the impact of tides on groundwater dynamics due to the widely distributed waterways and heterogeneous sediments in estuarine aquifers, is still needed. This study shows the tidal impact on groundwater dynamics in the Pearl River estuary in southeast China through wavelet and time series analysis. The groundwater level and electrical conductivity (EC), as well as tidal levels, were monitored in several observation wells and tidal stations to determine how the estuarine groundwater levels respond to tidal forcing. The results show that the groundwater fluctuations have short periodicities of 0.51 and 1 day corresponding to major tidal constituents of M2 (semidiurnal) and K1 and O1 (diurnal) signals, respectively. The significant impacts decrease with increasing distance inland of the locations of the wells. Additionally, the coherence analysis displays a higher correlation between tides and groundwater levels for the spring tide than for the neap tide. The tidal influences on groundwater EC are weak compared to those on groundwater levels. In addition, when the tidal level increases, the EC decreases in wells located in the estuarine entrance. This is related to the high salinity of retained paleo-seawater in the strata lenses. A conceptual model is proposed to illustrate the complex groundwater flow dynamics. The model may provide useful insights into the understanding of similar systems located in geographically different coastal regions.
Keywords: China; Coastal aquifers; Groundwater monitoring; Lunar semidiurnal tides; Tidal monitoring; fi=Energiatekniikka|en=Energy Technology|